2023
DOI: 10.3390/jof9060667
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Infections Associated with COVID-19

Abstract: The COVID-19 pandemic caused >6 million deaths worldwide, often from respiratory failure. Complications frequently occurred in hospitalized patients, particularly in the intensive care unit. Among these, fungal infections were a cause of high morbidity and mortality. Invasive aspergillosis, candidiasis and mucormycosis were the most serious of these infections. Risk factors included alterations in immune defense mechanisms by COVID-19 itself, as well as immunosuppression due to various therapies utilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…(This last one usually seen as ineffective based on clinical and laboratory experience due to its high minimal inhibiting concentration (MIC) [ 63 , 64 ]). Surprisingly, this combination has shown effectiveness not only in murine models [ 65 ], but also in promising case reports [ 66 , 67 ], even from highly endemic areas [ 28 ], despite being limited to ROCM and diabetic ketoacidosis patients [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(This last one usually seen as ineffective based on clinical and laboratory experience due to its high minimal inhibiting concentration (MIC) [ 63 , 64 ]). Surprisingly, this combination has shown effectiveness not only in murine models [ 65 ], but also in promising case reports [ 66 , 67 ], even from highly endemic areas [ 28 ], despite being limited to ROCM and diabetic ketoacidosis patients [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent genus causing clinical mucormycosis is Rhizopus (two main species) [ 25 ], followed by the genus Mucor (twelve species up to date) [ 24 ], Lichtheimia , and Rhizomucor ; other less frequent pathogenic species are occasionally reported [ 26 , 27 ]. The fast growth, airborne spores, and the thermotolerance of these ubiquitarian saprotroph moulds enable them to grow at human body temperature: these features explain their pathogenic activity in patients with specific risk factors, including SARS-CoV-2 infection and treatments [ 28 , 29 ], as listed in Table 1 [ 20 , 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38]48,50 Patients with significant immunocompromise are also at increased risk of IFD post recent viral infection, likely due to overlapping risk factors and viral-specific factors. Multiple observational studies have demonstrated increased rates of IFD in immunosuppressed patients post respiratory infection with influenza and respiratory syncytial virus [77][78][79] as well as severe acute respiratory syndrome coronavirus-2, 80 while others have shown an association between cytomegalovirus infection and IFD in the post-transplant setting. 81,82…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Mucormycosis is a rare angio-invasive fungal infection caused by a group of molds called mucormycetes [1,2]. The estimated global incidence varies from 0.005 to 1.7 cases per million people [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation varies according to the organ involvement, although it is well recognized that disease progression is marked by an aggressive and life-threatening course, emphasizing the critical importance of an early diagnosis and intervention [2]. COVID-19 is also associated with an increased risk of secondary fungal infections, such as aspergillosis, invasive candidiasis, and mucormycosis [1]. The pathophysiological and metabolic changes caused by SARS-CoV-2 and its therapeutic strategies have been implicated as facilitators of disease development.…”
Section: Introductionmentioning
confidence: 99%